Clinical diversity and treatment results in Tegumentary Leishmaniasis: A European clinical report in 459 patients. - Romain Guery; Stephen L Walker; Gundel Harms; Andreas Neumayr; Pieter Van Thiel; Jean-Pierre Gangneux; Jan Clerinx; Sara Karlsson Söbirk; Leo Visser; Laurence Lachaud; Mark Bailey; Aldert Bart; et al. (Public Library of Science (PLoS), 2021)
Background Cutaneous leishmaniasis (CL) is frequent in travellers and can involve oro-nasal mucosae. Clinical presentation impacts therapeutic management. Methodology Demographic and clinical data from 459 travellers infected in 47 different countries were collected by members of the European LeishMan consortium. The infecting Leishmania species was identified in 198 patients. Principal findings Compared to Old World CL, New World CL was more frequently ulcerative (75% vs 47%), larger (3 vs 2cm), less frequently facial (17% vs 38%) and less frequently associated with mucosal involvement (2.7% vs 5.3%). Patients with mucosal lesions were older (58 vs 30 years) and more frequently immunocompromised (37% vs 3.5%) compared to patients with only skin lesions. Young adults infected in Latin America with L. braziliensis or L. guyanensis complex typically had an ulcer of the lower limbs with mucosal involvement in 5.8% of cases. Typically, infections with L. major and L. tropica acquired in Africa or the Middle East were not associated with mucosal lesions, while infections with L. infantum, acquired in Southern Europe resulted in slowly evolving facial lesions with mucosal involvement in 22% of cases. Local or systemic treatments were used in patients with different clinical presentations but resulted in similarly high cure rates (89% vs 86%). Conclusion/significance CL acquired in L. infantum-endemic European and Mediterranean areas displays unexpected high rates of mucosal involvement comparable to those of CL acquired in Latin America, especially in immunocompromised patients. When used as per recommendations, local therapy is associated with high cure rates.